A family study of isolated cleft palate. Issue 5 (October 1982) - Carter, C O; Evans, K; Coffey, R; Roberts, J A; Buck, A; Roberts, M F
Abstract : A family study was based on 245 boy and 329 girl patients treated surgically for non-syndromic cleft palate between 1920 and 1929; 86 and 81 respectively were traced and had had children. These 167 were the probands for the family study and were interviewed in their homes. None was born to a consanguineous marriage. Altogether they had had 384 children of whom 11 had cleft palate (2.9 +/- 0.9%). They had 398 sibs of whom five had cleft palate, 117 grandchildren of whom one was affected, and 517 nephews and nieces of whom one was affected. This is the largest series yet available on which to base an estimate of the risks to children of patients with non-syndromic cleft palate. The risk is probably increased where a parent or sib of the proband is affected and increased to a lesser degree where a second or third degree relative is affected. The family patterns in these and other studies suggest that the aetiology of cleft palate is heterogeneous, with some families showing modified dominant inheritance. This is in contrast to cleft lip (+/- cleft palate) where the data are consistent with a multifactorial threshold model.